MAGNETIC FIELD BASELINE DETERMINATION FOR BAGHDAD CITY - TAHRER ADNAN ABDUL-MAJID; MAATH ISMAIL MAHMOOD; OMAR BURHAN AL-JARRAH (مجلة جامعة الانبار للعلوم الصرفة, 2014)
This research is conducted in Baghdad magnetic observatory – Jadriya by monitoring the measured total magnetic field around the clock for a whole year, for the purpose of defining magnetic baseline in order to identify the actual magnetic background for the site of Baghdad magnetic observatory. These observations show daily and seasonal variations in the field according to weather conditions and other factors in upper atmosphere. These variations are reflected directly on the earth magnetic field. Therefore, these readings have been plotted and analyzed to determine the magnetic baseline for the Baghdad observatory site. The average value was found to be equal to (45473.08) Gamma. It was shown that there is a unique value for each month of the year, that varies slightly according to sun activities during the summer.